2005
DOI: 10.1590/s0100-41582005000200008
|View full text |Cite
|
Sign up to set email alerts
|

Dispersão anemófila do fungo Lasiodiplodia theobromae em plantações de coqueiro

Abstract: RESUMONeste trabalho determinou-se a dispersão anemófila de conídios de Lasiodiplodia theobromae, agente causal da queima das folhas do coqueiro (Cocos nucifera), e sua relação com a precipitação pluviométrica. Para tanto, cinco armadilhas cata-vento e uma armadilha tipo Burkard, coletoras de esporos, foram instaladas nas entrelinhas de um coqueiral, a 1,80 m de altura do solo. Os conídios foram capturados em fitas transparentes, untadas com solução adesiva de gelvatol e vaselina. Semanalmente, as fitas foram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
1
6
0
1
Order By: Relevance
“…This observation is in accordance with Warwick et al (1993), who observed significantly higher growth rate of lesions caused by leaf blight in coconut hybrids in the dry season. The anemophilic dispersion of L. theobromae conidia has been reported to be strongly stimulated by rainfall, especially between 25 and 80 mm of monthly average rainfall, according to monitoring in the coconut production field (Correia and Costa, 2005). In the present study, the period from October to March presented the most favorable monthly averages rainfall for spore dispersion, as reported by Correia and Costa (2005), which in a large extent coincides with the period of greatest damage caused by leaf blight.…”
Section: Discussionsupporting
confidence: 67%
“…This observation is in accordance with Warwick et al (1993), who observed significantly higher growth rate of lesions caused by leaf blight in coconut hybrids in the dry season. The anemophilic dispersion of L. theobromae conidia has been reported to be strongly stimulated by rainfall, especially between 25 and 80 mm of monthly average rainfall, according to monitoring in the coconut production field (Correia and Costa, 2005). In the present study, the period from October to March presented the most favorable monthly averages rainfall for spore dispersion, as reported by Correia and Costa (2005), which in a large extent coincides with the period of greatest damage caused by leaf blight.…”
Section: Discussionsupporting
confidence: 67%
“…This tendency points out to the previous hypothesis that the pathogen is first introduced via randomly infected planting materials. Lasiodiplodia theobromae has been reported as an endophytic fungus (Baird and Carling 1998;Cilliers 1993;Mohali et al 2005;Mullen et al 1991;Rubini et al 2005) or as latent pathogen (Freire et al 2004;Khanzada et al 2004;Correa and Costa 2005;Cardoso et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In coconut crop, this pathogen is reported as the etiological agent of "coconut leaf blight" disease (Souza Filho et al, 1979), affecting the fruit production, causing premature lower leaves abscission, decreasing by 50% photosynthetic area, leaving bunches without support and, consequently, the fruits fall before harvest time (Correia and Costa, 2005;Monteiro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%